STUDENTS’ DIFFICULTIES IN LEARNING VOCABULARIES - Salam, Urai; Nurnisa, Nurnisa (Universitas Muhammadiyah Palembang, 2021)
This study was conducted among early English learners when they encountered problems in learning vocabularies. The purpose of this study was to uncover difficulties in learning English vocabularies faced by 33 Pesantren (boarding school) students in West Kalimantan. These students had low achievement in vocabulary mastery. The data were derived from questionnaires and interviews with selected students. The data revealed that the students experienced four difficulties, namely, pronouncing unique English sounds, spelling, memorizing long syllable-words, and understanding meaning of unfamiliar words.